Constantine and the Christian empire - Odahl, Charles Matson, 1944- (Roman imperial biographies., 2010)
"Charles Odahl's comprehensive knowledge of the literary sources and his extensive research into the material remains of the period mean that this volume provides a more rounded and accurate portrait of Christian emperor than ever before. Extensively illustrated and fully documented, Constantine and the Christian Empire has been a landmark publication in Roman imperial, early Christian, and Byzantine history. A genealogy chart, additional illustrations, an expanded final chapter, and updated notes and bibliography in this new edition allow this book to remain the standard account of the subject for years to come"--Provided by publisher.